The Reforming of housing and communal markets in the condition of economic crisis in Ukraine - Lyashenko, V. (Економічний вісник Донбасу, 2017)
The article is devoted to research of the problems of local markets of Ukraine. The paper identified the geographical limits of the local markets,their problems in the conditions of economic crisis, the problems of housing and communal services of Ukraine. The possible ways of solving the problem moments of industry. The need to reform the sector and the ineffectiveness of the reforms taking place in our time are caused. Стаття присвячена дослідженню існуючих проблем локальних ринків України. У статті визначено границі локальних ринків, їх проблеми, проблеми житлово-комунального господарства України. Запропоновано можливі шляхи вирішення проблемних моментів галузі. Обумовлено необхідність термінового реформування галузі і неефективність реформ, які проводяться в наш час. Статья посвящена исследованию существующих проблем локальных рынков Украины. В статье определены границы локальных рынков, их проблемы в условиях экономического кризиса, проблемы жилищно-коммунального хозяйства Украины. Предложены возможные пути решения проблемных моментов отрасли. Обусловлена необходимость срочного реформирования отрасли и неэффективность реформ, которые проводятся в наше время.